Oxygen concentration affects de novo DNA methylation and transcription in in vitro cultured oocytes - Naillat, Florence; Saadeh, Heba; Nowacka-Woszuk, Joanna; Gahurova, Lenka; Santos, Fatima; Tomizawa, Shin-Ichi; Kelsey, Gavin (Clinical epigenetics, 2021)
BACKGROUND: Reproductive biology methods rely on in vitro follicle cultures from mature follicles obtained by hormonal stimulation for generating metaphase II oocytes to be fertilised and developed into a healthy embryo. Such techniques are used routinely in both rodent and human species. DNA methylation is a dynamic process that plays a role in epigenetic regulation of gametogenesis and development. In mammalian oocytes, DNA methylation establishment regulates gene expression in the embryos. This regulation is particularly important for a class of genes, imprinted genes, whose expression patterns are crucial for the next generation. The aim of this work was to establish an in vitro culture system for immature mouse oocytes that will allow manipulation of specific factors for a deeper analysis of regulatory mechanisms for establishing transcription regulation-associated methylation patterns. RESULTS: An in vitro culture system was developed from immature mouse oocytes that were grown to germinal vesicles (GV) under two different conditions: normoxia (20% oxygen, 20% O2) and hypoxia (5% oxygen, 5% O2). The cultured oocytes were sorted based on their sizes. Reduced representative bisulphite sequencing (RRBS) and RNA-seq libraries were generated from cultured and compared to in vivo-grown oocytes. In the in vitro cultured oocytes, global and CpG-island (CGI) methylation increased gradually along with oocyte growth, and methylation of the imprinted genes was similar to in vivo-grown oocytes. Transcriptomes of the oocytes grown in normoxia revealed chromatin reorganisation and enriched expression of female reproductive genes, whereas in the 5% O2 condition, transcripts were biased towards cellular stress responses. To further confirm the results, we developed a functional assay based on our model for characterising oocyte methylation using drugs that reduce methylation and transcription. When histone methylation and transcription processes were reduced, DNA methylation at CGIs from gene bodies of grown oocytes presented a lower methylation profile. CONCLUSIONS: Our observations reveal changes in DNA methylation and transcripts between oocytes cultured in vitro with different oxygen concentrations and in vivo-grown murine oocytes. Oocytes grown under 20% O2 had a higher correlation with in vivo oocytes for DNA methylation and transcription demonstrating that higher oxygen concentration is beneficial for the oocyte maturation in ex vivo culture condition. Our results shed light on epigenetic mechanisms for the development of oocytes from an immature to GV oocyte in an in vitro culture model.
Keywords: In vitro culture; Transcription; oocyty; metylace DNA; Mice, Inbred C57BL; Animals; kyslík; Oxygen; Mice; myši inbrední C57BL; Normoxia; Oocyte; IVM techniky; Female; 5% oxygen; In Vitro Oocyte Maturation Techniques; ženské pohlaví; DNA methylation; DNA Methylation; Mouse; zvířata; Transcriptome; transkriptom; Oocytes; myši